Smart Gas Sensors: Recent Developments and Future Prospective - Boyang Zong; Shufang Wu; Yuehong Yang; Qiuju Li; Tian Tao; Shun Mao (Nano-Micro Letters)
Highlights Recent developments of advanced electronic and optoelectronic gas sensors are introduced. Sensor array with artificial intelligence algorithms and smart gas sensors in “Internet of Things” paradigm are highlighted. Applications of smart gas sensors in environmental monitoring, medical and healthcare applications, food quality control, and public safety are described.